2023
DOI: 10.1037/sgd0000558
|View full text |Cite
|
Sign up to set email alerts
|

The gender/sex 3×3: Measuring and categorizing gender/sex beyond binaries.

Abstract: Critiques of gender/sex measurement tend to focus on the questions researchers ask, including their binaristic, static nature, or overfocus on/erasure of transgender/cisgender status. The questions matter, as does the way gender/sex responses may be categorized, which has received less focus. In this article, we report on the "Gender/Sex 333," which we developed via two studies to produce a novel framework for conceptualizing, measuring, and categorizing gender/sex. It represents two intersecting dimensions: "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…In future studies, we would add a second question (i.e., are you transgender?) (Lombardi & Banik, 2016) or a Gender/Sex 3x3 Model (Beischel et al, 2022) to better describe our sample.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, we would add a second question (i.e., are you transgender?) (Lombardi & Banik, 2016) or a Gender/Sex 3x3 Model (Beischel et al, 2022) to better describe our sample.…”
Section: Discussionmentioning
confidence: 99%
“…This includes trans men, transmasculine people, trans women, transfeminine people, and some nonbinary people. Some trans people are nonbinary and not all nonbinary people are trans (Beischel et al., 2022). We use transmasculine/trans man and transfeminine/trans woman to describe participants unless the research explicitly includes nonbinary identities.…”
Section: Methodological and Epistemological Features Of Research On H...mentioning
confidence: 99%
“…For example, research that includes transgender and cisgender categories is an improvement over cisnormative research that presumes participants are cisgender. However, transgender and cisgender are often positioned as the only two options for gender trajectory (i.e., a person's relationship to their sex assigned at birth; Beischel, Schudson, et al, 2022). In contrast, research has demonstrated that not everyone falls into one of these two categories, and that an "allogender" category is a useful addition (Beischel, Schudson, et al, 2022), echoing narratives and lived experiences (Bornstein, 1994;Darwin, 2020;Diamond & Butterworth, 2008).…”
Section: Multiplicitiesmentioning
confidence: 99%